Synthesis, characterization and catalytic activity of palladium supported on bleaching clay - Amirul Edham, Roslee (2012)
Bleaching clay (BC) is one example of phyllosilicate clay that consists of two tetrahedral sheets sandwiching a central octahedral sheet. Palladium (Pd) is proposed to adsorb on the layers of BC by adsorption process to form the palladium supported in bleaching clay (Pd-BC) structure. The layer structure of BC with the ability of exchangable cation allowed the adsorption process of Pd. In this research, pretreatment of BC involved the acid content analysis using ion chromatography (IC) and acid-base titration, fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA) to determine its physical and chemical characteristics. The adsorption process is done by adding PdC1 2 solution of variable Pd contents (1, 2, 3 % w/w) into BC-ethanol suspension and stirred for 4 hours, before the mixture is filtered, washed three times with distilled water and dried at room temperature. The characterization with X-ray diffraction (XRD) is meant to study layer spacings, while N 2 sorption is to obtain surface areas and pore structure. The hydrogenation process of palm oil was performed using Pd-BC as catalyst in order to test the catalytic activity of Pd-BC. The catalyst is dissolved in isopropanol before the mixture is bubbled with H 2 gas for 60 minutes, then palm oil is added at room temperature and the hydrogenation process is continued for another 90 minutes. After that the hydrogenated palm oil is extracted with hexane and esterified with methanol in NaOH before the product is analyzed by gas chromatography (GC) to determine the percentage of fatty acid methyl esters (FAME). The acid-base titration and IC analysis of BC revealed that BC sample has about 1.26 to 1.8213 % w/w of sulphuric acid, while FTIR and TGA confirmed the presence of clay mineral in BC and its thermal process. The adsorption process with different Pd contents varied the distribution of Pd cations between the layers of BC and its adsorption capacity. Pd-BC samples have smaller surface area, but larger layer spacing than BC. Pd-BC samples are achieved for catalytic hydrogenation of palm oil and cause lower percentage of C18:2 FAME through higher percentage of C18:0 and C18:1 FAMEs.